A non-destructive and efficient transfer method for preparing 2D materials samples for transmission electron microscopy study. (20th August 2022) - Lyu, Fengjiao; Tang, Bin; Li, Xuan; Chen, Qing
Abstract: Studying two-dimensional (2D) materials using transmission electron microscopy (TEM) is necessary and very important in many aspects. However, some 2D materials are not resistant to acids or alkalis, which are widely used in normal wet transfer techniques to transfer the exfoliated 2D nanosheets onto the TEM grids. On the other hand, dry stamping method can damage the holey carbon film on the TEM grids. In this article, we present a non-destructive, efficient, and widely applicable transfer method for preparing the TEM samples of the exfoliated 2D materials. Our method only uses the heat-release tape, PMMA, and blue Nitto tape. Neither acid nor alkali is involved in our method, therefore, impurities and damage can be avoided to the greatest extent. The method is also very efficient and can be accomplished in less than 30 min after the exfoliation of the 2D materials. This method is particularly useful for preparing the TEM samples of the 2D materials that are not resistant to acids and alkalis. The present method is also applicable to various 2D materials and various substrates.